Relationship between energy allocation and gametogenesis in Aulacomya atra (Bivalvia: Mytilidae) in a sub-Antarctic environment - Pérez, Analía Fernanda; Boy, Claudia Clementina; Curelovich, Jessica Natalia; Pérez Barros, Patricia; Calcagno, Javier Ángel (Revista de biología marina y oceanografía)
Gametogenesis and temporal variation in energy allocation to different organs were analyzed in Aulacomya atra from the Beagle Channel (Tierra del Fuego, Argentina). Our results show that A. atra presents an extended spawning period from late winter to spring when the lowest value of mantle-gonad index (MGI) and maximum number of spawned individuals were observed. The MGI in mature males increased as the energy density of the mantle-gonad (EDMG) decreased, indicating an increase in mass of lower energy values. In contrast, the MGI in mature females increased as EDMG increased, indicating an increase in mass of higher energy values. Consequently, males and females reached a similar energy content of the mantle-gonad (ECMG) by means of different strategies: males have gonads of larger size but with lower energy by unit of mass than females. Besides, we observed a decrease in the digestive gland index (DGI) in concordance with an increase in the MGI of mature individuals, and a trend towards the depletion of ED and EC in the digestive gland during gonadal maturation. Our results evidence the role of the digestive gland as an energy reservoir and a different energy allocation strategy between sexes during gonadal maturation. Se analizó la gametogénesis y la variación temporal en la asignación de energía a diferentes órganos de Aulacomya atra del Canal Beagle (Tierra del Fuego). El periodo de desove de A. atra se extendió desde el final del invierno hasta la primavera, cuando el MGI (Índice gónada-manto) resultó mínimo y el número de individuos desovados, máximo. En los machos maduros el incremento del MGI coincidió con un descenso en la densidad energética del manto-gónada (EDMG), lo que está relacionado con un aumento de masa con menor energía. En hembras maduras el incremento de MGI se relaciona con un aumento de masa con valores más altos de energía, que determina el aumento de la EDMG. Durante la maduración gonadal existen diferentes estrategias de asignación de energía en ambos sexos, aunque se alcanza similar ...